Building sustainable tourism through collaborative governance: Study on Sumberbiru tourism village, wonosalam district, Jombang Regency - Sholahuddin Hadi Sucipto; Irfan Kharisma Putra; Ahmad Bachtiar; Inayatul Fikriyah (Cv. Nashir Al-kutub Indonesia, 2024)
This study aims to analyze the role and contribution of various parties in the implementation of collaborative governance for the development of tourist destinations in Sumberbiru Tourism Village, Jombang Regency. Several issues found in this study include the lack of effectiveness in managing tourist destinations, suboptimal institutions, and limited accessibility. This study uses a qualitative approach with a case study method and SWOT analysis to formulate a tourism development strategy based on field conditions. The results of the study show that the government plays a key role as a driver of collaboration between stakeholders, involving academics, the business sector, local communities, and the media. Each party contributes according to their respective roles and expertise, through various programs such as training, mentoring, provision of capital, and construction of supporting tourism facilities. The tourism development program created through this collaboration has proven effective in overcoming most of the existing challenges, although it has not completely resolved all the problems faced by the tourist village.